Calcium phosphate formation from sea urchin - (Brissus latecarinatus) via modified mechano-chemical (ultrasonic) conversion method - (:unkn) unknown (My University, 2013)
This study aims to produce apatite structures, such as hydroxyapatite (HA) and fluorapatite (FA), from precursor calcium phosphates of biological origin, namely from sea urchin, with mechano-chemical stirring and hot-plating conversion method. The produced materials were heat treated at 800 °C for 4 hours. X-ray diffraction and scanning electron microscopy (SEM) studies were conducted. Calcium phosphate phases were developed. The SEM images showed the formation of micro to nano-powders. The experimental results suggest that sea urchin, Brissus latecarinatus skeleton could be an alternative source for the production of various mono or biphasic calcium phosphates with simple and economic mechano-chemical (ultrasonic) conversion method.
Keywords: Calcium phosphates; Mechano-chemical method; Sea urchin; Ultrasonic